Augmented Reality Birdwatching in Mindo - Villamarín, Genaro Sebastian Sulca (2020)
The project reported in this dissertation presents the development of an Android mobile application to be used for birdwatching in Mindo - Ecuador. The application has as target audience tourists and as main goal to share information about the species that inhabit the aforementioned place to improve tourist experience; it provides routes to follow with points of interest in which the users can find bird species. In addition to this, the application provides scientific information and highlights the most important characteristics of bird species, information about the threats that may be exposing these species to extinction and multimedia content like images, videos and sounds of those species. As a distinctive feature, this application uses augmented reality to enhance birdwatching experience; it allows the user to interact in a different way with nature and offers the opportunity to perceive virtual 3D models of some birds and take photos of it to share on social networks or simply to save on the device. To manage all the content of the application, a web-based backoffice was also developed, to add, edit or remove routes, spots and species including their information, images, videos and sounds. The augmented reality, together with the user-friendly interface make the application very interactive and attractive to the user, likewise, the backoffice allows a simple administration of the content.